INFLUENCE OF CORTICAL-VEGETATIVE REGULATION MECHANISMS ON LACTATE, PYRUVATE CONTENT AND THEIR CORRELATION IN SOWS’ BLOOD - Postoi, R. V.; Karpovskyi V.І.; Shostya, A.M.; Usenko, S. O.; Karunna, T.I.; Shaferivsky, B. S. (Scientific Progress & Innovations, 2019)
Individual features of the nervous system activity cause different levels of metabolism in the body, re-sistance to stress factors and the speed of adaptation to changing environmental conditions. The purpose of the article is to find out the influence of cortical-vegetative regulation mechanisms on carbohydrate metabo-lism indices in sows’ blood. Types of higher nervous activity in 3 year old dry sows of Large white breed were determined by the method of conditioned food reflexes; the autonomic neurotony was investigated by a trigeminovagal test. The content of lactate and pyruvate was determined in blood plasma of sows; correla-tion and variance analyses of the obtained data were conducted to evaluate the relationship and influence of cortical-vegetative regulation mechanisms. Our research results have shown that there is a correlation be-tween indices of conditioned reflex activity, the type of cardiac rhythm autonomic regulation in sows and lactate content in blood plasma. Probable differences in lactate content in the blood plasma between sows with different type of heart rate autonomic regulation were revealed. According to the variance analysis data, vagotony had a probable effect on lactate content in the blood plasma – η2х=0.34 (р<0.05). In addition, there was a close relationship between plasma lactate content and vagotony (r=0.91; p<0.01) and sympath-icotony (r=-0.64; p<0.01). Depending on the typological features of higher nervous activity, it was estab-lished that in sows with strong balanced mobile type, lactate content in blood plasma was lower (by 15.06–15.96 %; р<0.05) as compared with sows of strong balanced inert and weak types. It has been found that the mobility of excitation and inhibition processes in the cerebral cortex is related to lactate content in the blood plasma (r=-0.46; p<0.05) and has a probable impact on it (η2х=0.36; p<0.01). Instead, cortical-vegetative regulation mechanisms do not have a probable impact on pyruvate content in the blood plasma and lactate/pyruvate ratio. Thus, new scientific data on the influence of cortical-vegetative regulation mecha-nisms on separate indices of carbohydrate metabolism in dry sows’ blood of Large white breed have been obtained.